Influence Of Demographic Variables on Organizational Commitment of Women Teachers of Higher Secondary School: A Study on Chhattisgarh State - Yadav, Bharat; Kalpana Priya; Jyoti Verma (Journal of Innovation in Education and Social Research, 2026)
Organizational commitment is one of the determinants that affect the effectiveness and stability of schools. For higher secondary schools, teachers' organizational commitment greatly affects student achievement, institutional culture, and the quality of education. Organizational commitment is the psychological bond and devotion that teachers have for their school, including their desire to do good and stay with the organization. Different demographic and occupational factors like gender, age, years of teaching experience, subject specialization, type of management, and residential area may influence teachers' commitment differently. Additionally, training opportunities, continuous professional development (CPD), and salary structure are critical factors in influencing teachers' motivation and long-term participation. This study aims to study the organizational commitment of women teachers of higher secondary school in relation to type of school, type of institutional residence, discipline, maritial status and teaching experience. It is important to know how these variables influence the commitment of teachers in order to enhance teacher retention, motivation, and general school performance. The study utilizes a descriptive research design using standardized questionnaires to collect data from a representative sample of female teachers. Findings are anticipated to yield insights into what factors most strongly correlate with commitment levels, thus informing evidence-based policy-making and institutional interventions aimed at boosting teacher involvement and satisfaction.